INTEGRATED ASSESSMENT OF STATIN-ASSOCIATED MUSCLE DAMAGE PREDICTORS IN PATIENTS WITH ISCHEMIC HEART DISEASE - V. I. Petrov; O. N. Smuseva; Yu. V. Solovkina (Столичная издательская компания, 2015)
Aim. To assess the risk factors of statin-associated muscle damage in patient with ischemic heart disease. Material and methods. 258 patients with ischemic heart disease treated with statin were included into the study. Total plasma creatine kinase levels were measured and SLCO1B1*5 genotyping was performed. Relationship between statin therapy and adverse events was evaluated by Naranjo algorithm. Results. Patients with muscle symptoms received statins significantly longer (48.8 vs 11.9 months, р<0.0001) and in higher doses, than patients without muscle pain/weakness. There were not significant differences in creatine kinase levels between patients with and without muscle symptoms. Patients with SLCO1B1*5 genotype were revealed in both groups, but more often (58%) among patients with muscle symptoms. Patients with abnormal C allele having muscle symptoms received statins significantly longer, than these without muscle signs (54.7 vs 13.9 months, р=0.0028). Conclusion. Association between occurrence of muscle symptoms and SLCO1B1*5 allele carriership, statin dose and therapy duration was revealed. Creatine kinase examination was not valuable for finding of statin-induced muscle damage.